Actors' joint for the local development: case of the Ripc (Revista LIDER, 2020)
There is analyzed the problem of sustainability of the Network of Productive Innovation of the Coconut, local development policy promoted by the Ministry of Science, Technology and Innovation, since 2000, in the municipality Tocópero, Falcón State, Venezuela, through research territorial prospective focused on articulating the key actors involved in the management of the network.